WILL TO TRUTH IN THE PHILOSOPHY OF PRAGMATISM - D. Y. Snitko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Since the clear statement of the will-to-truth question as an existential has not been fulfilled before, this article is devoted to the solution of such a task. In connection with the above, the purpose of the study is to analyze the phenomenon of will to truth in the philosophy of pragmatism. This involves the following tasks: the definition of the basic principles of understanding the truth in the works of theorists of pragmatism; analysis of the phenomenon of «will to believe» in pragmatism; development and selection of the phenomenon of will to truth, its essence and factors within the framework of pragmatic philosophy. Methodology. The author used analytical, comparative and phenomenological methods in the research. Originality. For the first time, the paper articulates the existential of the will to truth, its essence and factors on the subject of the philosophy of pragmatism. Conclusions. The analysis of the phenomenon of «will to believe» in pragmatism proves that it can be interpreted as «will to truth», because belief in truth of something in pragmatism is inseparable from the truth itself and practice. Within the framework of pragmatic philosophy, the author has determined the essence of will-to-truth phenomenon, which is understood as the aspiration of man to a stable and relevant to reality and his own goals persuasion in relation to himself and reality. The main factors of this phenomenon in pragmatism are doubts (doubts are defined as a prerequisite for the establishment of belief (beliefs), which gives a person confidence in the positive decision of certain life tasks) and persistent belief (truth) that enables a person to succeed and achieve his goals. That is precisely the result of the man's will to truth: the existence of man is determined by the fact that a person prefers to know how to act.